Antero-posterior localization of the pyramidal tract in the internal capsule in a living patient - León S., Fidias E; Pradilla A., Gustavo (Investigación Clínica, 2013)
A lacunar infarction occurred in the posterior limb of the internal capsule in a 33-years-old Colombian woman, showed an antero-posterior (A-P) course of the corticospinal pathway. Anatomical and histological studies had suggested this course, but to the author’s knowledge, this could be the first reported case of a living patient with such features, confirming those previous reports about them.